Given exp
=x^2-8x+x-8
=x(x-8)+1(x-8)
=(x+1)(x-8)
2007-03-13 01:51:11
·
answer #1
·
answered by alpha 7
·
1⤊
0⤋
Completing the square method
x² - 7x - 8 = 0
x² - 7x - 8 + 8 = 0 + 8
x² - 7x = 0
x² - 7x + ______ = 8 + ______
x² - 7x + 49 / 4 = 8 + 49 / 4
(x - 7/2)(x - 7/2 = 32/4 + 49/4
(x - 7/2)² = 81/4
(âx - 7/2)² = ± â81 / â4
x - 7/2 = ± 9/2
x - 7/2 + 7/2 = 7/2 ± 9/2
x = 7/2 ± 9/2
- - - - - - - - - -
Solving for +
x = 7/2 + 9/2
x = 16/2
x = 8
- - - - - - - -
Solving for -
x = 7/2 - 9/2
x = - 2/2
x = - 1
- - - - - - - - - - - - -
Method 2
x² - 7x - 8 = 0
Find the sum of the middle term
x = 1
Multiply the first term by the last term and factor
1 x 8 = 8
Factors of 8 = 1, 2, 4, 8
- 8 and + 1 satisfy the sum of the middle term
x² - 7x - 8
x² + x - 8x - 8
x(x + 1) - 8(x + 1)
(x - 8)(x + 1)
- - - - - - -
Roots
x - 8 = 0
x - 8 + 8 = 0 + 8
x = 8
- - - - - - -
Roots
x + 1 = 0
x + 1 - 1 + 0 - 1
x = - 1
- - - - - - - - s-
2007-03-13 02:32:47
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
Let's make your problem more general ax^2+bx+c where a, b, c can be any integer ie 0, +-1, .... . You want 2 integers that can multiply to get a and two integers that multiply to get c. List them out, cross multiply the results and add them to get the b coefficient.
In your case. x^2 - 7x - 8
a=1, b=-7, c=-8
2 integers that multiply to get a(1) would be 1 x 1. So list it vertically.
1
1
2 integers that multiply to get a(-8) would be 1x-8. So list it vertically next to the previous combination to form a grid.
1 1
1 -8
Now when you cross multiply and add up the sum 1x-8 + 1x1 = -7 which is equal to the b coefficient.
Now just read across the grid horizontally. (1x + 1)(1x-8) and your done.
x^2 -7x -8 = (x+1)(x-8)
Now order doesn't matter. Whenever you factor, it takes some trial and error to find the right "grid". Practice often helps speed up this process.
2007-03-13 02:07:09
·
answer #3
·
answered by Jason C 2
·
0⤊
0⤋
It is x in the 2nd power x².
they cannot write it in the proper form so they write x^2.
and for those who need more info about this, they supposed to use the alt key 253 then the power of 2 will appear like this ².
in this case:
factoring:
x²-7x-8
= x²-8x + 1x-8
=x(x-8)+ 1(x-8)
=(x+1) (x-8) ...................ans
and if you want to find out the value of x, you may use
the quadratic formula for this.
ax+bx+c=0
x = -b+-[b²-4ac]/2a
there will be two answers:
x = 8 and the other answer will be x = -1
2007-03-13 02:18:59
·
answer #4
·
answered by edison c d 4
·
0⤊
0⤋
What 2 numbers multiplied equals -8 and added equal -7?
-1 and 8: no
1 and -8: yes
x^2-7x-8
=(x+1)(x+(-8))
=(x+1)(x-8)
2007-03-13 01:58:21
·
answer #5
·
answered by misterbean 2
·
0⤊
0⤋
is that 2X? What is the symbol between X and 2?
If it is supposed to be x+2-7x-8...solve for x
-6x -6 = 0
-6x = 6
x = -1
2007-03-13 01:54:35
·
answer #6
·
answered by Curly 4
·
0⤊
0⤋
x²-7x-8 =
(x - 8)(x + 1)
><>
2007-03-13 02:00:31
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
x^2 - 7x - 8
what two numbers multiply to 8 and subtract to 7? 8 and 1
(x+1)(x-8)
you can foil it to check your answer if you would like
2007-03-13 02:03:18
·
answer #8
·
answered by Bill F 6
·
0⤊
0⤋
x^2-7x-8
x^2-8x+1x-8
x(x-8)+1(x-8)
(x+1)(x-8)
are the factors of the eqn
2007-03-13 01:53:45
·
answer #9
·
answered by PUNJABI ROCKS 2
·
0⤊
0⤋
you should find two numbers that have the summation equal to -7 and multiplication equal to -8. those two numbers are -8 and +1. after finding these two numbers you can write:
(x-8)(x+1)
2007-03-13 02:02:25
·
answer #10
·
answered by arman.post 3
·
0⤊
0⤋